Audit on results of tympanoplasty: experience at a tertiary centre - Singh, Anjali; Chaudhary, Ashvanee; Singh, Vishwambhar (International Journal of Research in Medical Sciences, 2020)
Background: Chronic otitis media can be associated with various extracranial and intracranial complications. It has led to rise in number of people living with discharging ear and reduced hearing. Methods: Authors have shared their 3 years’ experience of a single tertiary institute regarding disease burden and management and results. This is a retrospective study including 500 cases of mucosal type of chronic otitis media and underwent tympanoplasty at the study institute. Follow-up records were kept for at least 6 months. Results: Graft uptake rate after 6 months follow-up was 86.2%. Cartilage tympanoplasty was performed for revision cases and had good results. Average air-bone gap closure was 17 dB. It is a simple surgery which can be performed in day care OT without any significant intra-op or post-op complication. Conclusions: Surgical treatment is significantly useful to reduce the disease burden due to chronic otitis media.